Mangrove restoration priorities across coastal landscape typologies - ASWIN RAHADIAN; LILIK BUDI PRASETYO; YUDI SETIAWAN; CECEP KUSMANA (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Rahadian A, Prasetyo LB, Setiawan Y, Kusmana C. 2026. Mangrove restoration priorities across coastal landscape typologies. Biodiversitas 27 (3): d270305. https://doi.org/10.13057/biodiv/d270305. Mangrove restoration in Indonesia is a new episode and a milestone paradigm in the management of natural resources and the coastal environment after the era of timber extraction. It is crucial for advancing biodiversity conservation, strengthening climate change mitigation, and refining future restoration practices from conceptual, technical, and methodological perspectives. This study aims to develop restoration approaches implemented in Indonesia and to propose an integrated framework based on landscape typology. Mangrove restoration approaches were identified through a comprehensive literature review and a priority assessment using the PROMETHEE method across landscape typologies, based on sustainability indicators derived from stakeholder interviews. We integrate our PROMETHEE results with a geospatial approach to produce a spatially explicit priority map. Various mangrove restoration approaches applied in Indonesia have demonstrated both strengths and limitations. Despite their partial nature, they are evidence-based and have been tested across diverse locations. The results of the study revealed that, in deltas and estuaries, protection approaches prioritize natural regeneration; on the open coast, ecological engineering is prioritized; in the backward zone, intensive planting is prioritized; and, in addition to intact mangroves, priority protection with species enrichment is prioritized. Compared to the partial approach, integrating mangrove restoration with landscape typologies will maximize ecological success and long-term socio-economic sustainability.